Mathematical representation ability and curiosity of 8th graders in the 7E-Learning Cycle Model with realistic approaches - Astuti, Dina Dwi; Waluya, Budi; Soedjoko, Edy (Unnes Journal of Mathematics Education, 2020)
This study aimed to test the effectiveness of 7E-learning cycle learning with realistic approaches for students' mathematical representation ability and describe the students' mathematical representation ability from the view of students' curiosity. This study used a mixed-method with a concurrent embedded model. The population of this study was 8th graders in a Junior High School in Patebon, Kendal. Random sampling was used to obtain 32 students for the experiment class and 32 students for the control class. For the qualitative analysis, two students for each high, medium, and low curiosity level were selected. Questionnaires, tests, interviews, and documentation were used to collect data. T-test, classical completeness Z-test, the mean difference test, and proportions different tests were used to analyze the data quantitatively. Meanwhile, qualitative data were analyzed using data reduction, data display, conclusion drawing, and verification. The results show that 7E- learning cycle learning with realistic approaches affected students' mathematical representation abilities positively. The study also revealed that students with high, medium, dan low curiosity levels show different perform in mathematics representation.